2022
DOI: 10.1038/s41467-022-33482-8
|View full text |Cite
|
Sign up to set email alerts
|

Migration of solidification grain boundaries and prediction

Abstract: Solidification processing is essential to the manufacture of various metal products, including additive manufacturing. Solidification grain boundaries (SGBs) result from the solidification of the last liquid film between two abutting grains of different orientations. They can migrate, but unlike normal GB migration, SGB migration (SGBM) decouples SGBs from solidification microsegregation, further affecting material properties. Here, we first show the salient features of SGBM in magnesium-tin alloys solidified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Their found that the formation of DDC is associated with the straight MGB morphology. There is no DDC in the tortuous MGB and creep-like morphology DDC at the tripe point of the MGB [15] , [16] . So, controlling the weld composition, grain size and morphology are efficient ways to improve the microstructure and mechanical properties of Inconel 690 alloy.…”
Section: Introductionmentioning
confidence: 95%
“…Their found that the formation of DDC is associated with the straight MGB morphology. There is no DDC in the tortuous MGB and creep-like morphology DDC at the tripe point of the MGB [15] , [16] . So, controlling the weld composition, grain size and morphology are efficient ways to improve the microstructure and mechanical properties of Inconel 690 alloy.…”
Section: Introductionmentioning
confidence: 95%
“…Figures 7(A)-(C) shows the weld bead geometry of the laser beam weldment at top middle and centre of the weld bead with full penetration, and figure 7(D) shows the bead width with a length of 2.9 mm of the weldment, in mid span with a width of 1.02 mm and depth shows with full penetration. The solidification grain barrier (SGB) [22] may be seen in the middle of the fusion zone. The greater laser power density and travel speed are both thought to be caused by the SGB in the middle of the fusion zone.…”
Section: Weld Qualitymentioning
confidence: 99%